Understanding Digital Literacy in Religious Content on Social Media: @generation_muda_nu and @kuntummagazine Study - Marfuah Sanityastuti; Rika Lusri Virga; Latifa Zahra (Profetik: Jurnal Komunikasi, 2024)
In Indonesia, the development of social media use has not been directly proportional to the skills in using digital media or digital literacy. It is not uncommon for the information disseminated or received to invite controversy, which results in hostility and crime. Using qualitative descriptive research methods with the results that the understanding of digital literacy and the display of social media content on public accounts, namely the @generasi_muda_nu account and the @kuntummagzine account, in managing Instagram using interview methods with the managers of each account and documentation and content display analysis. This research also found that @generasi_muda_nu and @kuntummagazine accounts understand the diversity of digital media contexts. Both accounts also include cognitive abilities in content posts and involve new creations in content. It's just that @generasi_muda_nu is much more able to take advantage of these creations by maximizing other features of Instagram, such as Instagram TV. However, the account manager @generasi_muda_nu is much more active because the account gets more comments from its followers than the @kuntumamgazine account. Both accounts have also been creative in displaying content in the style of young people; the critical attitude of the manager has also been is only discussed briefly. The account manager's social responsibility is displayed in several posts through source quotes and account identities written on each uploaded content